On the space resolution of the μ-RWELL. (12th August 2021) - Bencivenni, G.; Capoccia, C.; Cibinetto, G.; de Oliveira, R.; Farinelli, R.; Felici, G.; Gatta, M.; Giovannetti, M.; Lavezzi, L.; Morello, G.; Poli Lener, M.; Tskhadadze, E.
Abstract: In micro-pattern gaseous detectors (MPGD) the evaluation of the space resolution with the charge centroid method provides large uncertainty when the incident particle is not perpendicular to the readout plane. An improvement of the position reconstruction is given by the microTPC (μTPC) algorithm: the three-dimensional reconstruction of the particle track inside the detector drift gap is performed using the arrival time of the induced signals on the readout. In this work we report the application of this method to the μ-RWELL detector that, combined with the charge centroid, allows to achieve an almost uniform resolution below 100 μm over a wide angular range.